BANKING LEADERSHIP TRANSFORMATION IN THE DIGITAL ERA: A DIGITAL SOCIOLOGY PERSPECTIVE ON BANK NTT HEAD OFFICE, KUPANG - Hamdan Saleh Batjo; alosyius liliweri; rahmat laan; syarifuddin darajad; Wahid Hasyim TRA Beni; Ahmad Atang (SOSIOEDUKASI, 2026)
The digital transformation of banking is often understood as a technological change, even though it is a social process that involves shifting values, norms, and power relations in dimensional organizations that have not been touched much by banking leadership studies, especially in Regional Development Banks in the Eastern Indonesia region. This research aims to examine leadership transformation in PT Bank Pembangunan Daerah Nusa Tenggara Timur (Bank NTT) through the perspective of digital sociology. The research uses a qualitative approach with a case study method, with primary data from in-depth interviews with directors and heads of divisions as well as participatory observations, and secondary data from internal documents and official publications of Bank NTT. The results of the study show that the success of Bank NTT's digital transformation is supported by leadership capacity that develops multidimensionally, strategic actions that integrate infrastructure strengthening, service innovation based on local needs, and organizational culture transformation, as well as sensitivity to the social dynamics of the NTT community including the digital divide, changes in social relations, and the construction of digital trust. These findings confirm that banking leadership in the digital age is evolving into collaborative and participatory network leadership. This research contributes to offering an analytical framework that integrates transformational leadership, digital sociology, and functionalism to understand digital transformation in regional banks more holistically